Quantitative determination of the spring entropy effect and its indication of the conformational change of polymer coils with varying concentration in aqueous poly(N-isopropylamide) solutions. Issue 10 (14th February 2019) - Song, Li; Lin, Jiaxiang; Liu, Panpan; Li, Jingqing; Jiang, Shichun; Huang, Dinghai
Abstract : Entropy effect is deduced from the distinctive demixing enthalpy behavior in different concentration regions of PNIPAM aqueous solution and interpretated as the conformational change of polymer coil. Abstract : The lower critical solution temperature (LCST) phase separation behaviors of thermosensitive poly( N -isopropylacrylamide) (PNIPAM) aqueous solutions were investigated by power-compensation differential scanning calorimetry (DSC). The entropic effect and hence the change of swelling state of PNIPAM polymer coils in homogeneous concentrated aqueous solutions with varied solution composition was elucidated by the isothermal enthalpy demixing recovery behaviors in distinct concentration regions.